2003
DOI: 10.1074/jbc.m300805200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Phosphatidylinositol 3-Kinase, Akt/Protein Kinase B, FRAP/Mammalian Target of Rapamycin, and Ribosomal S6 Kinase 1 Signaling Pathways by Thyroid-stimulating Hormone (TSH) and Stimulating type TSH Receptor Antibodies in the Thyroid Gland

Abstract: Thyroid-stimulating hormone (TSH) regulates the growth and differentiation of thyrocytes by activating the TSH receptor (TSHR). This study investigated the roles of the phosphatidylinositol 3-kinase (PI3K), PDK1, FRAP/mammalian target of rapamycin, and ribosomal S6 kinase 1 (S6K1) signaling mechanism by which TSH and the stimulating type TSHR antibodies regulate thyrocyte proliferation and the follicle activities in vitro and in vivo. The TSHR immunoprecipitates exhibited PI3K activity, which was higher in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 55 publications
3
53
0
Order By: Relevance
“…Differences in cell culture conditions could be amenable for this discrepancy, which otherwise remains obscure. However, it is clearly reminiscent of the observation that TSH, a glycoprotein hormone structurally related to FSH, stimulates p70S6K1 in a PI3K-dependent manner, without activating Akt (Suh et al, 2003). Furthermore, the muscarinic M3 receptor mediates p70S6K1 activation and enhances its phosphorylation on the T389 residue through an mTOR-dependent mechanism, in an astrocytoma cell line.…”
Section: Discussionmentioning
confidence: 97%
“…Differences in cell culture conditions could be amenable for this discrepancy, which otherwise remains obscure. However, it is clearly reminiscent of the observation that TSH, a glycoprotein hormone structurally related to FSH, stimulates p70S6K1 in a PI3K-dependent manner, without activating Akt (Suh et al, 2003). Furthermore, the muscarinic M3 receptor mediates p70S6K1 activation and enhances its phosphorylation on the T389 residue through an mTOR-dependent mechanism, in an astrocytoma cell line.…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, Aktmediated TCS phosphorylation is not critical for mTOR activity during Drosophila development (Dong and Pan, 2004). Furthermore, at least two different ligands -TSH acting on thyroid epithelial cells (Suh et al, 2003) and prostaglandin F2a in luteal cells (Arvisais et al, 2006) can activate mTOR without exerting any appreciable effect on Akt. Finally, in transformed B lymphocytes mTOR activation is mostly, if not completely, PI3K/ Akt-independent .…”
Section: Discussionmentioning
confidence: 99%
“…They include the CD40 ligand, 28 thyroid-stimulating hormone, 29 fibroblast growth factor-9, 30 polycystein-1, 31 and prostaglandin F2a. 32 In regard to malignant lymphocytes, we found that in anaplastic T/null-cell lymphomas that expresses a chimeric, constitutively activated form of the anaplastic lymphoma kinase, the kinase induces mTORC1 activation.…”
Section: Discussionmentioning
confidence: 99%